Penerapan Latihan Shuttle Run pada Atlet Lari Jarak Pendek di Club Linggau Runners - Amanda Fransiska; Muhammad Suhdy; Wawan Syafutra (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2021)
This study aimed to determine the application of shuttle run training to short-distance runners at the Linggau Runners club. This research method is quantitative. The data collection technique used a test, namely the initial test and the final test to determine the improvement of short-distance running ability. The analysis technique uses the z test. The collected data were analyzed using the z-test at a significant level of = 0.05. The results showed that the average increase in short-distance running athletes was 6.50 and based on the test criteria zcount 10.16 > ztable 1.64 was declared increased. In conclusion, the ability of athletes to run short distances after the shuttle run exercise was applied significantly increased. Keywords: Shuttle Run, Short Distance Run